Construction labour's productivity indicator to the project success: a literature review / Syarifah Nur Nazihah Syed Jamalulil ... [et al.] - Syed Jamalulil, Syarifah Nur Nazihah; Ab. Wahid, Abdul Muhaimin; Nasharudine, Mohammad; Jaffar, Noraidawati; Rosli, Nur Atikah (2022)
The productivity of labour is an extremely critical project performance measurement tool used in the construction industry. How good the productivity is on site will largely impact the overall performance of a project. Construction industry is well known for its labour-intensive activities, as this industry relies heavily on the skills of its workforce. Majority of the construction activities are based on labour performance. Thus, contractors must use all available knowledge, expertise, and management skills in order to improve project performance. However, it has been noticed that at construction sites, contractors have ignored the productivity of their labours and its effects on the overall productivity. Following that situation, this research was conducted to identify the factors that affect the productivity of construction labour and to find out the impacts of construction labour's productivity to the project performance. Therefore, literature review is carried out as a research methodology to achieve the research objectives. The result indicates that manpower, management, motivation, and project factors are the most important factors that affect the productivity of construction labour. Besides that, time, cost, and quality are the major impacts of construction labour's productivity to the project performance. Hence, this research posits that it is essential to highlight the factors and impacts of construction labour's productivity in the construction industry to improve the project performance in the future.